2020
DOI: 10.1097/sla.0000000000004632
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Dementia After Exposure to Anesthesia and Surgery in the Elderly

Abstract: Objective: The aim of this study was to determine whether surgery and anesthesia in the elderly may promote Alzheimer disease and related dementias (ADRD). Background: There is a substantial conflicting literature concerning the hypothesis that surgery and anesthesia promotes ADRD. Much of the literature is confounded by indications for surgery or has small sample size. This study examines elderly patients with appendicitis, a common condition that strikes mostly at random after controlling for some known asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…EditordPostoperative delirium is characterised by acute and usually reversible cognitive disturbance with fluctuating changes in attention and level of consciousness, with an incidence of ~20% in older patients after major, non-emergent surgery. 1 It is recognised as a significant contributor to adverse outcomes in older hospitalised patients, as delirium is associated with prolonged hospitalisation, discharge to skilled care facilities, and persistent cognitive decline. 2,3 As surgical populations continue to age, the incidence of postoperative delirium and related complications will likely increase.…”
Section: Correspondence -E269mentioning
confidence: 99%
See 2 more Smart Citations
“…EditordPostoperative delirium is characterised by acute and usually reversible cognitive disturbance with fluctuating changes in attention and level of consciousness, with an incidence of ~20% in older patients after major, non-emergent surgery. 1 It is recognised as a significant contributor to adverse outcomes in older hospitalised patients, as delirium is associated with prolonged hospitalisation, discharge to skilled care facilities, and persistent cognitive decline. 2,3 As surgical populations continue to age, the incidence of postoperative delirium and related complications will likely increase.…”
Section: Correspondence -E269mentioning
confidence: 99%
“…EditordWe previously examined the association between the exposure of surgery and anaesthesia for appendicitis and the subsequent development of Alzheimer's disease and related dementias (ADRD). 1,2 We chose to focus on appendicectomy because appendicitis appears to occur fairly randomly (acting as a natural experiment), and its sequelae are generally not long term, unlike other procedures possibly needed as a result of underlying illnesses that may affect long-term outcomes. Literature has suggested that there are common pathways of neurodegeneration in Parkinson's disease (PD) and ADRD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective studies on the risk for developing Alzheimer disease and related dementias (ADRD) after surgery with anesthesia have yielded conflicting results. A new study using a Medicare database compared this risk in nearly 55,000 patients aged 68 to 77 years without ADRD who required an appendectomy for appendicitis (treatment group) versus nearly 275,000 patients matched for age and multiple other factors who had no signs of appendicitis and no appendectomy prior to matching (control group) [1]. After 7.5 years follow-up, the treatment group actually had a lower rate of ADRD (7.6 versus 8.6 percent).…”
Section: Surgery With Anesthesia Does Not Increase Risk Of Developing Dementia (April 2021)mentioning
confidence: 99%
“…Besides, elderly surgical patients are more likely to have preexisting AD or be at risk for developing it (Işik, 2015). On the other hand, there are clinical studies that fail to support the association of anesthesia and surgery with AD (Avidan and Evers, 2011;Sprung et al, 2013Sprung et al, , 2020Aiello Bowles et al, 2016;Silber et al, 2020). However, some animal experiments have been reported where individuals with AD may develop cognitive impairment after anesthesia and surgery, but the mechanism is not clear (Zhang et al, 2017;Miao et al, 2018;Kim et al, 2021).…”
Section: Introductionmentioning
confidence: 99%